Serum neuronal specific enolase as a biomarker in differentiating the side of brain lesion in acute hemorrhagic stroke: a hospital based study - Baidya, Omkar Prasad; Tiwari, Sunita; Usman, Kauser (International Journal of Research in Medical Sciences, 2016)
Background: Neuronal specific Enolase (NSE) is the neuronal form of the glycolytic enzyme enolase. This study has been conducted to see the role of serum NSE in differentiating the side of brain lesion within 24 hours of acute hemorrhagic stroke onset. Methods: The study was conducted in collaboration with the Department of Physiology and Medicine after Ethical clearance from December 2013 to April 2015. Our study group consists of 35 acute hemorrhagic stroke patients (clinically and radio logically confirmed) irrespective of age and sex, admitted in Emergency Unit, Medicine Department within 24 hours of stroke symptom onset. The patients were undergone plain CT scan brain on admission to confirm the diagnosis and the side of the lesion in brain. Serum NSE for these patients was estimated by using NSE Human ELISA Kit, in the Department of Physiology. Results: In this study, serum NSE bears a positive significant correlation to the hematoma volume in brain (r=0.786, p<0.001) and to the National Institute of Health Stroke Scale (NIHSS) (r=0.44, p=0.008). However, there is no significance difference between the serum NSE in right hemispheric brain lesion compared to left hemispheric brain lesion (p=0.597). Conclusions: Serum NSE within 24 hours of stroke onset can reflect the volume of brain lesion and severity of neurological deficit but cannot differentiate the side of brain lesion in these patients.